Probing size exclusion mechanisms of complex hydrocarbon mixtures: The effect of altering eluent compositions - KARACA ALBAYRAK, FATMA (My University, 2007)
This paper describes the application of size exclusion chromatography (SEC) to petroleum residue samples that are incompletely soluble in 1-methyl-2-pyrrolidinone (NMP). The limitations arising from the use of tetrahydrofuran, pure chloroform, and pure NMP have been reviewed. The SEC of polycyclic aromatic hydrocarbons (PAHs) in pure chloroform was observed to give longer elution times with increasing molecular mass, the opposite of the expected trend. Because the smallest molecules of coal tars are known to be PAHs, SEC can only be of use in investigating the larger molecules of unknown mass if the elution behavior of the smaller standard PAH relates to the calibration using polymers. The work relies on the observation that the NMP/chloroform mixtures dissolved both the heavier fractions of a coal tar pitch and the whole of a petroleum asphaltene, completely at the low concentrations needed for SEC. The first tests of the new SEC calibration have been carried out using a Mixed-E column and pure NMP, pure chloroform, and mixtures of these solvents as eluents. Most of the work was carried out at an NMP-to-chloroform volume ratio of 5:1. These initial results show elution times of polystyrene standards and PAH on a Mixed-E column using mixtures of NMP and chloroform as well as these solvent separately. The elution behavior of a vacuum residue in three different eluents is presented. The excluded peak observed in chromatograms of a vacuum residue and an asphaltene became more intense when using the mixed solvent compared to SEC using pure NMP as eluent. Synchronous UV-fluorescence spectra confirmed that petroleum derived components with the largest chromophores are insoluble in NMP but soluble in chloroform and observable by UV-fluorescence spectroscopy. The data suggest that the fraction insoluble in NMP was of larger aromatic cluster size and presumably attached to very large aliphatic groups that rendered the material insoluble in NMP but soluble in both chloroform and the mixed solvent. © 2007 American Chemical Society.